Vergewaltigt
This broadcast reports on rape as a tactic of war in the former Yugoslavia and its effect on Muslim women, the main victims of this type of war crime in Bosnia. The gynecological clinic in Zenica is focused on, highlighting its role as a center for the termination of unwanted pregnancies. Doctors from the clinic, rape victims, and Imams are all interviewed, showing the effect of rape on the Bosnian society, and, specifically, the Bosnian Muslim views on rape and abortion. The victims featured range from young to old and are almost entirely Muslim.